PENGARUH PENGAPLIKASIAN SHADING DAN TINT PADA RIAS WAJAH MALAM HARI TERHADAP BENTUK WAJAH BULAT - Handika Putri, Tri Gitia; Rahmiati, Rahmiati; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
Research background of some problems especially round face shape (grouped face shape is not ideal). This problem arises when doing makeup for the night, because in this case required correct correction so that all the deficiencies on the face can be covered through makeup. The aim of this research is to analyze the application of shading and tint on night face makeup to round face shape with use of one layer, two layers, and three layers. This type of research is quasi experiment with non equivalent Control Design form. The object of this study is students of state university of Padang who has a round face shape aged 18-22 years. Sampling by purposive sampling technique.Sources of data of this research there are six panelists that provide indicator-based marking in the assessment sheet used as a research instrument. Before the hypothesis test is necessary to test the analysis statement to see the normality and homogeneity, to test the hypothesis used anava test and continued Duncan test.The results of this study indicate that there are significant effects of all treatment groups studied is the value of f arithmetic>f table. It is advisable to use tan tint shading preferably with the use of two layers because it is more efficient and effective in terms of time and energy.Keywords: shading and tint, night makeup to round face shape